Medicinal Plants with Psychoactive Properties: A Comprehensive Review - Rimi, Fakhray Jahan; Fardous, Jannatul; Zaman, Fahmida; Patwary, Md. Kawchar Ahmed; Maisha, Mahajabin Tabassom (Sciences of Phytochemistry, 2026)
Medicinal plants have been used in traditional medicine to alleviate a range of neurological and psychological disorders. Numerous plant-derived phytochemicals are known to modulate central nervous system activity by interacting with neurotransmitters, receptors, and neurochemical pathways. This review provides a comprehensive overview of medicinal plants with psychoactive properties, their major bioactive constituents, mechanisms of action, therapeutic potential, toxicity concerns, and regulatory considerations. Literature was collected from scientific databases, including PubMed, Scopus, ScienceDirect, Web of Science, and Google Scholar, using relevant keywords on psychoactive medicinal plants and neuropharmacological activities. Twenty medicinal plants commonly associated with anxiolytic, antidepressant, sedative, hallucinogenic, or cognition-enhancing effects were reviewed. Major phytochemical classes identified included alkaloids, flavonoids, terpenoids, phenolic compounds, cannabinoids, and saponins. Several plants, such as Withania somnifera, Cannabis sativa, Valeriana officinalis, Psilocybe cubensis, and Passiflora incarnata, have been reported to exhibit neuropharmacological activities in preclinical and limited clinical studies, through modulation of serotonergic, dopaminergic, GABAergic, and endocannabinoid systems. In addition to psychoactive effects, many reviewed plants exhibited antioxidant, anti-inflammatory, neuroprotective, and adaptogenic properties. However, despite promising pharmacological findings, most available evidence remains preclinical, with limited clinical validation regarding efficacy, safety, standardization, and long-term use. This review highlights the therapeutic prospects and current limitations of psychoactive medicinal plants and emphasizes the need for further experimental and clinical investigations for safe and evidence-based therapeutic applications.